Prosthetic Complications in a Patient with Papillon-Lefevre Syndrome Treated with Dental Implants: A Case Report - Tanous, Michel; Alikhasi, Marziyeh (Regeneration, Reconstruction & Restoration (Triple R), 2020)
Introduction: Patients with Papillon-Lefevre syndrome (PLS) lose their teeth because of periodontal disease followed by alveolar bone resorption. On the other hand, this complicate implant treatment, force the surgeon to insert implants more palatally, or to do more extensive surgical procedure. Case report: A 24-year-old female diagnosed with PLS received an implant supported metal-acrylic prosthesis which was failed due to the dissatisfactory design and unpleasant influence on the patient function and esthetics. The prosthesis was substituted by a new designed one, fabricated by CAD/CAM technology to compensate the implants positions and fulfill patient function and esthetics. Results: The patient followed up the day after delivery, one week, and each 6-month, without any reported prosthetic complications or bone loss after three-year follow-up appointment. Conclusion: We presented the ability to restore esthetics and functions of a patient suffering from severe bone loss due to PLS by using the bone grafts and dental implants.